Leukocyte population dynamics in response to ovalbumin peptide immunization in DO11 mice - Mitrescu, Laura M., author; Schenkel, Alan R., author (Colorado State University. Libraries, 2006)
DO11 mice are transgenic mice, which have a T cell receptor (TCR) capable of specifically recognizing the protein ovalbumin. CD4 and CD8 T lymphocytes carrying this TCR be easily traced, making these mice a useful animal model in which to follow an immune response. Injection of ovalbumin peptide in adjuvant initiates an immune response, leading to changes in the various lymphocyte subsets responding to the stimulus. We expected to see an increase in the number of effector cells shortly after immunization, followed by the development of an ovalbumin-specific memory population of CD4 lymphocytes over long term. In order to monitor the different leukocyte populations participating in the response, we used flow cytometry coupled with surface staining for relevant cell markers. As expected, effector cell numbers showed a statistically significant increase at the 10-day timepoint, although both ovalbumin specific and nonspecific cells responded. This may be due to addition of adjuvant. over a 6-month period, immediate effectors disappeared and most cell populations returned to baseline levels. However, we could not find a CD4 memory cell population in the spleen. In addition to T cell,s we also monitored changes in other leukocyte population that might participate in the immune response. Future aims are to examine the immune response to ovalbumin in PECAM deficient mice. PECAM is a cell adhesion molecule, which mediates several steps of the immune response. The data generated by this project in wild-type mice will be used as a control to data obtained in PECAM knockout mice in order to clarify the role of PECAM in inflammation.
Keywords: Leucocytes; Immune response; T cells -- Receptors